Lossless sharing visual cryptography - Bin YU; Zheng-xin FU (Tongxin xuebao)
According to the information loss during the secret image sharing process, the lossless sharing visual crypto-graphy was proposed. The optimizations of two parameters were simplified into one parameter. The matrices translation algorithm and the integer programming model were designed. Furthermore, the pixel expansion optimization algorithm was realized. The experimental results show that the algorithm achieves the optimal pixel expansion under lossless shar-ing, and can be used in general access structure.